Students’ Perceptions on English Fun Fair as an Implementation of Project-Based Learning in Speaking for Social Purposes Classes - Ardela Indri Apriliani; Listyani Listyani (Soegijapranata Catholic University, 2020)
English Fun Fair is one of the implementation models in Project-Based Learning (PBL) which involves learning through various tasks and collaborative learning. Particularly, the project was implemented in Speaking for Social Purposes classes at an English Language Education Program, at a private university in Central Java, Indonesia. The study aimed to investigate students' perceptions of the influence of English Fun Fair which consisted of the benefits and challenges of the project. The participants of the study were fifty (50) students from 2016, 2017, and 2018 Academic Year who had taken Speaking for Social Purposes course and had done English Fun Fair. To gain data more deeply, the researchers used a qualitative method. The instruments used were open-ended questionnaires and semi-structured interviews. In the questionnaires, the participants answered some questions related to this study. After that, as a follow-up of the answers in the questionnaires, the researcher did interviews. Besides that, the data showed that improving speaking skills was the most dominant benefit mentioned by the participants. However, problems in speaking skills also became a challenge which they experienced a lot. Expectantly, the findings from this study can give views for EFL teachers about the benefits of this project and for EFL students can develop their speaking and other skills.